The Effort of Musi Banyuasin to Gain Interest in the International World - Agustina, Tia; Azhar; Lionardo, Andries; Rivai, Ferdiansyah; Manggarsari, Yuniarsih (Journal of Paradiplomacy and City Networks, 2022)
This study investigated the Musi Banyuasin Regency Government’s role as a regional actor in international affairs. Regional governments can develop the region and affect the regional economy thanks to paradiplomacy, one of the phenomena in international relations that seeks to involve international relations actors. This research was grounded in the paradiplomacy theory proposed by Pertti Joenniemi and Alexander Sergunin. This study employed a descriptive qualitative method, aiming to provide a general overview of the subject of study by using data collected in their raw form without applying any analysis and drawing any pertinent conclusions. Primary data were collected from the Musi Banyuasin Regency Government. In contrast, secondary data came from the Musi Banyuasin Regency Government’s official website and news articles discussing the research subject. Following the findings, the Government of Musi Banyuasin Regency fulfilled its role as an international relations actor by implementing paradiplomatic methods such as promoting a positive image of the region through participation in international forums, joining international organizations, and collaborating with them.